Anaemia is associated with an increased risk for caesarean delivery. Issue 2 (29th August 2019) - Adam, Ishag; Kheiri, Sumeya; Sharif, Manal E.; Ahmed, Abdel B.A.; Rayis, Duria A.
Abstract: Objective: To investigate the association between anemia and cesarean delivery. Methods: A case‐control study was conducted in Saad Abu‐Alela Hospital in Khartoum, Sudan from March 1 to November 30, 2107. The cases were women who had cesarean delivery; women who delivered vaginally were the controls. Obstetrics history was gathered using a questionnaire. Results: There was no significant difference in age, parity, residence, job, education, and newborn gender between women who delivered by cesarean (n=130) and women who delivered vaginally (n=260). While mean (SD) of the body mass index (29.3 (5.4) kg/m 2 vs 26.3 (5.6) kg/m 2, P <0.001) was significantly higher, hemoglobin level (103.0 (8.0) g/L vs 107.0 (8.0) g/L, P =0.001) was significantly lower in women who delivered by cesarean compared with women who delivered vaginally. In logistic regression analyses, age, gravidity, occupation, education, history of miscarriage, and newborn gender were not associated with cesarean delivery; overweight (adjusted odds ratio [AOR] 2.30, 95% confidence interval [CI] 1.24–4.26), obesity (AOR 7.17, 95% CI 3.64–14.13) and anemia (AOR 2.45, 95% CI 1.47–4. 11) were associated with cesarean delivery. Conclusion: The significant association between anemia and cesarean delivery has important implications for the prevention and treatment of anemia among these women. Abstract : While age, gravidity, occupation, education, and history of miscarriage were not associated with cesarean delivery; overweight, obesity and anemia were associated with cesarean delivery.